Flexible Ureterorenoscopy and Laser Lithotripsy in a Patient with a Stone in the Transplanted Kidney: A Case Report - Marjan Marić; Tomislav Kuliš; Luka Penezić; Vedran Andrijašević; Ivica Mokos; Željko Kaštelan (Acta Clinica Croatica, 2023)
We report a case of a 31-year-old patient with obstructive ureterolithiasis in a transplanted kidney, treated endoscopically with flexible ureterorenoscopy and laser lithotripsy. The patient presented with biochemical signs of acute renal failure and ultrasonographically detected hydronephrosis. Emergency nonenhanced computed tomography scan revealed an obstructive 5-mm stone in the ureter of the transplanted kidney with resulting hydronephrosis. The patient received a double J stent to relieve allograft obstruction. Since the stone size was deemed favorable for conservative treatment, the patient was discharged. Two months later, he was readmitted for leucopenia caused by mycophenolate mofetil. After recuperation of his white blood cell count, he was referred to extracorporeal shock wave lithotripsy, but since the stone was radiolucent, an endoscopic procedure was indicated. Retrograde endoscopic flexible ureterorenoscopy with ‘dusting’ of the stone was successfully performed. One year after the procedure, the patient was stone free and with good allograft function.